Mechanistic insights of the controlled release capacity of polar functional group in transdermal drug delivery system: the relationship of hydrogen bonding strength and controlled release capacity - Zheng Luo; Chao Liu; Peng Quan; Degong Yang; Hanqing Zhao; Xiaocao Wan; Liang Fang (Elsevier, 2020)
Background: Hydrogen bonding interaction was considered to play a critical role in controlling drug release from transdermal patch. However, the quantitative evaluation of hydrogen bonding strength between drug and polar functional group was rarely reported, and the relationship between hydrogen bonding strength and controlled release capacity of pressure sensitive adhesive (PSA) was not well understood. The present study shed light on this relationship. Methods: Acrylate PSAs with amide group were synthesized by a free radical-initiated solution polymerization. Six drugs, i.e., etodolac, ketoprofen, gemfibrozil, zolmitriptan, propranolol and lidocaine, were selected as model drugs. In vitro drug release and skin permeation experiments and in vivo pharmacokinetic experiment were performed. Partial correlation analysis, fourier-transform infrared spectroscopy and molecular simulation were conducted to provide molecular details of drug-PSA interactions. Mechanical test, rheology study, and modulated differential scanning calorimetry study were performed to scrutinize the free volume and molecular mobility of PSAs. Results: Release rate of all six drugs from amide PSAs decreased with the increase of amide group concentrations; however, only zolmitriptan and propranolol showed decreased skin permeation rate. It was found that drug release was controlled by amide group through hydrogen bonding, and controlled release extent was positively correlated with hydrogen bonding strength. Conclusion: From these results, we concluded that drugs with strong hydrogen bond forming ability and high skin permeation were suitable to use amide PSAs to regulate their release rate from patch.